Interactionism and Social Harmonization in Wonomulyo as the Multiethnic City - Masdar, Muhammad; Harifuddin, Harifuddin; Iskandar, Abdul Malik; Azus, Faidah; Usman, Ahmad (SCAD Independent, 2024)
This study aims to (1) analyze the meaning of symbolic interactionism in multiethnic community members in the Wonomulyo District and (2) describe the sociometric form of symbolic interactionism in multiethnic communities in the Wonomulyo District. This research is qualitative research using a sequential exploratory design, namely qualitative-quantitative. Collecting data using in-depth interview techniques, observation, and literature study. Data analysis used a three-step technique: reduction, categorization, and conclusion. The results are (1) the interactionism in multiethnic society is built on openness, friendship, and kinship, and everyone likes this attitude so that social harmony is built; (2) The sociometric form of symbolic interactionism in Wonomulyo as a multiethnic city that Javanese as the dominant culture, namely open attitude, friendship, and kinship created social harmonization. The conclusion is that dominant culture plays a role in shaping societal tendencies, such as the harmonious Javanese culture, which is conditioning the culture of the Wonomulyo people always to be harmonious.